IMPLEMENTASI PROGRAM PEMBIASAAN BACA AL-QURAN SEBELUM PELAKSANAAN PEMBELAJARAN DI MADRASAH ALIYAH SUMATERA THAWALIB PARABEK - Darmawan Siregar , Agung; Trisno, Bambang; Jendrizal, Jendrizal (CV. ADIBA AISHA AMIRA, 2024)
In this modern era, technological progress is increasingly rapid and human activities are always increasing, so that nowadays many people forget about religious activities, such as reciting the Koran, giving alms, and even not praying. Then with influence like this, it even reaches children, who follow the times. This research is entitled